Investigation on the properties of nano copper matrix composite via vacuum arc melting method. (19th October 2017) - Liu, Yi; Leng, Jinfeng; Wu, Qirui; Zhang, Shaochen; Teng, Xinying
Abstract: Copper and copper matrix composites (CMCs) are widely used as electrical contact materials in electrical switch systems due to their excellent electrical properties. Graphene has great mechanical, physical and electrical properties, which is competent as an attractive reinforcing material for fabricating CMCs. Therefore, graphene was added to CMCs to improve the mechanical properties. In this study, graphene-reinforced copper matrix composites (Gr/Cu composites) were obtained. The x Gr/Cu ( x   =  0, 0.1, 0.3 and 0.5 wt.%) composites were fabricated via the vacuum arc melting method and compared the performance of them. The mechanical properties and electrical properties were obtained by measuring the hardness and conductivity. The microstructure of Gr/Cu composites was observed by optical microscopy (OM) and scanning electron microscopy (SEM). With the addition of graphene from 0 wt.% to 0.5 wt.%, the densities of materials decreased from 97.0% to 95.7%. With the increasing of graphene content, the hardness of composites increased at beginning and then decreased. In this range of adding amount, the hardness of 0.3Gr/Cu composite was up to 66.8 HB and increased by 15.4% compared to Al2 O3 /Cu composites without graphene. With the addition of graphene powder, the international annealing copper standard IACS% of Gr/Cu composites decreased from 86.16 to 69.86. The range of decline and the percentage of decline range are middle and 18.9%, respectively.